Authoring Performance The Director in Contemporary Theatre - Sidiropoulou, Avra 1972- (United Kingdom Palgrave : Macmillan, 2011)
A historical, theoretical, and comparative study of the emergence of the director-as-author phenomenon, posing questions of authorship and redefining the relationship between 'playwright' and the director-playwright
2
Keywords: Theatre